2018
DOI: 10.1590/s0102-865020180010000006
|View full text |Cite
|
Sign up to set email alerts
|

Thoracotomy compared to laparotomy in the traumatic diaphragmatic hernia. Systematic review and proportional methanalysis

Abstract: Purpose: To evaluate the most used approach to treat traumatic diaphragmatic ruptures, and in which one the requirement to assess the second cavity is more frequent. Methods: Systematic review, observational studies. Outcomes: moment of approach, most commonly via addressed and the requirement to open the other cavity. Bases searched: Lilacs, Pubmed, Embase, Clinicaltrials.gov and Web of Science. Statistical analysis: StatsDirect 3.0.121 software. Results: Sixty eight studies (2023 participants) were included.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 41 publications
0
10
1
5
Order By: Relevance
“…[2, 10, 27] One recent systematic review that included 2,023 patients showed that, for acute TDH, an abdominal approach is more frequent than a thoracic one, whereas in the chronic phase, a thoracic approach is more frequent; the requirement to open the second cavity is similar in both approaches. [28] However, this is inconsistent with the results of our study. The choice of approach differs greatly in the literature and depends largely on the first department visited and the preferences of the surgeon.…”
Section: Discussioncontrasting
confidence: 99%
“…[2, 10, 27] One recent systematic review that included 2,023 patients showed that, for acute TDH, an abdominal approach is more frequent than a thoracic one, whereas in the chronic phase, a thoracic approach is more frequent; the requirement to open the second cavity is similar in both approaches. [28] However, this is inconsistent with the results of our study. The choice of approach differs greatly in the literature and depends largely on the first department visited and the preferences of the surgeon.…”
Section: Discussioncontrasting
confidence: 99%
“…In certain cases, transthoracic approach may be necessary to release long-standing adhesions. Trauma literature describes an abdominal approach (laparoscopy or laparotomy) for early presentations, and thoracic approaches for long-standing diaphragmatic hernias due to the likely presence of dense adhesions in the chest [10].…”
Section: Discussionmentioning
confidence: 99%
“…De no disponer de cirugía mínimamente invasiva, el abordaje recomendado en las HDT agudas sería una laparotomía en la línea media, ya que permite explorar toda la cavidad abdominal 3,6,11,13 y en más del 89% de los casos la HDT se asocia a lesiones intrabdominales 14 . También en las HDT agudas se puede iniciar con un abordaje torácico cuando se identifiquen lesiones asociadas en el tórax 15 . En las HDT crónicas con sospecha de lesión abdominal, el abordaje debe ser transabdominal 3,6 .…”
Section: A H E a D O F P R I N T Discusiónunclassified
“…Por otra parte, las HDT izquierdas crónicas y las HDT derechas no complicadas pueden ser manejadas de mejor forma mediante cirugía torácica videoasistida o por toracotomía, debido a las adherencias y al contenido ya organizado 4,11 . En un metanálisis reciente, Silva y col analizaron 68 estudios que incluían 2.023 pacientes con HDT, hallando que el abordaje abdominal es el más utilizado (75%) en la fase aguda, ya sea por laparotomía o laparoscopia, y el abordaje torácico mediante toracotomía o toracoscopia el más común (69%) en la fase crónica 15 , coincidiendo con otros estudios 4,6,7 .…”
Section: A H E a D O F P R I N T Discusiónunclassified
See 1 more Smart Citation